1992
DOI: 10.1143/jjap.31.l293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Pulling Rate on Formation of Crystal-Originated “Particles” on Si Wafers

Abstract: It was recently revealed that singularities (crystal-originated “particles”) formed on Si wafers after SC1 cleaning originate from some defects in crystals and were perceived by laser particle counters. In this paper, the size distribution of crystal-originated “particles” is examined in detail by means of repeated SC1 cleanings. It is shown that, as the crystal pulling rate becomes faster, the size distribution of crystal-originated “particles” shifts toward smaller size, and the total number of origins of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…3,7-10 However, since crystal originated particles ͑COP͒ were reported, 11 a great deal of work has been devoted to determining the actual origin of the oxide defects. [12][13][14][15][16][17][18][19][20][21][22][23][24] We recently used a copper decoration method to show that these oxide defects are caused by an empty octahedral structure. 25 We analyzed the content of the octahedral structure by using energy-dispersive x-ray spectroscopy ͑EDS͒ and showed that the structure is void.…”
Section: Introductionmentioning
confidence: 99%
“…3,7-10 However, since crystal originated particles ͑COP͒ were reported, 11 a great deal of work has been devoted to determining the actual origin of the oxide defects. [12][13][14][15][16][17][18][19][20][21][22][23][24] We recently used a copper decoration method to show that these oxide defects are caused by an empty octahedral structure. 25 We analyzed the content of the octahedral structure by using energy-dispersive x-ray spectroscopy ͑EDS͒ and showed that the structure is void.…”
Section: Introductionmentioning
confidence: 99%
“…A higher concentration of DIO 3 was more effective in removing organic wax. Although DIO 3 is very effective in removing organic contaminants, DIO 3 shows too low removal rates on thick wax layer. It took more than 45 min at least to reach a film thickness less than 500Å which indicates the ozone reaction is diffusion controlled process.…”
Section: Resultsmentioning
confidence: 99%
“…• For defect count only, AFM is the slowest and WIS is about 1093 times faster than that of DDS at the optimized settings (2) and 90 times faster than that of DDS at the projected settings (3). However, if the DDS image size can be increased and the ICCD camera exposure time can be reduced further, the scanning time for DDS is projected to be in the same order to that of the WIS system.…”
Section: G Dds-afm Combination For Defect Detection Localization Anmentioning
confidence: 99%
“…However, there is another type of "particle" commonly found by the laser particle counter on the Czochralski-grown single crystal silicon wafer surface, which is typically called crystal originated "particles" (COPs) [1], [2]. COPs have been Manuscript recognized as surface defects or micropits, which originate from grown-in defects [3]. It was found that the presence of COPs is the main cause of gate oxide integrity (GOI) degradation [4], [5].…”
Section: Introductionmentioning
confidence: 99%